PENINGKATAN HASIL BELAJAR SMASH BOLAVOLI MELALUI PEMBELAJARAN BERBASIS MEDIA - Arisman STKIP Pamane Talino Ngabang (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2019)
This study aims to improve student learning outcomes in learning volleyball smash through media-based learning. The method used is action research design Kemmis and Taggart. The subjects in this study were students of SMA Santo Tomas X totaling 38 people.Research in cycle 1 meeting performed 3 times, starting from initial tests to measure students' abilities before the given action. After the act of learning undertaken, researchers gave a final test on the students and the result is a complete student as many as 16 students with a percentage of completeness 42.11%, when compared to the success criteria specified actions, namely 80% of the study conducted in cycle 1 could not be said to be successful , The study was continued to cycle 2 with slight changes and additions to the previous learning of each action and the second cycle will be implemented as much as 3 meeting. The final test in cycle 2 showed excellent improvement as many as 32 students get finished with a percentage of 84.21%. In other words, this study also no longer need to be continued because it is in accordance with the criteria of success of 80%.Based on these results we can conclude that: 1) through media-based learning can improve student learning outcomes in learning smash volleyball, 2) the application of media-based learning gives students the convenience and can motivate students in implementing the learning.